Effect of Trehalose and Lactose Treatments on the Freeze-Drying Resistance of Lactic Acid Bacteria in High-Density Culture - Shumao Cui; Mengyu Hu; Yuanyuan Sun; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Hao Zhang (Microorganisms, 2022)
Freeze-drying is a commonly used method in commercial preparations of lactic acid bacteria. However, some bacteria are killed during the freeze-drying process. To overcome this, trehalose and lactose are often used as protective agents. Moreover, high-density culture is an efficient way to grow bacterial strains but creates a hypertonic growth environment. We evaluated the effects of trehalose and lactose, as a primary carbon source or as an additive in fermentation, on the freeze-drying survival of Lactobacillus fermentum FXJCJ6-1, Lactobacillus brevis 173-1-2, and Lactobacillus reuteri CCFM1040. Our results showed that L. fermentum FXJCJ6-1 accumulated but did not use intracellular trehalose in a hypertonic environment, which enhanced its freeze-drying resistance. Furthermore, genes that could transport trehalose were identified in this bacterium. In addition, both the lactose addition and lactose culture improved the freeze-drying survival of the bacterium. Further studies revealed that the added lactose might exert its protective effect by attaching to the cell surface, whereas lactose culture acted by reducing extracellular polysaccharide production and promoting the binding of the protectant to the cell membrane. The different mechanisms of lactose and trehalose in enhancing the freeze-drying resistance of bacteria identified in this study will help to elucidate the anti-freeze-drying mechanisms of other sugars in subsequent investigations.